2017
DOI: 10.1039/c7mb00476a
|View full text |Cite
|
Sign up to set email alerts
|

Methods for monitoring and measurement of protein translation in time and space

Abstract: Regulation of protein translation constitutes a crucial step in control of gene expression. Here we review recent methods for system-wide monitoring and measurement of protein translation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 79 publications
0
33
0
Order By: Relevance
“…For this reason, the concentration of mRNA was used as a reflection of the levels and activity of the encoded proteins [3]. However, transcriptome analyses revealed that the regulation of gene expression at the mRNA level exists [51], as there are differences in protein levels over time and between clonally identical cells that may result from, e.g. promoter binding, decay of mRNA, translational rate, and protein degradation index [52].…”
Section: Mrna-protein Correlationmentioning
confidence: 99%
“…For this reason, the concentration of mRNA was used as a reflection of the levels and activity of the encoded proteins [3]. However, transcriptome analyses revealed that the regulation of gene expression at the mRNA level exists [51], as there are differences in protein levels over time and between clonally identical cells that may result from, e.g. promoter binding, decay of mRNA, translational rate, and protein degradation index [52].…”
Section: Mrna-protein Correlationmentioning
confidence: 99%
“…To study the effect of CR on the temporal protein translation, we decided to isolate mRNA associated with ribosomes. There are several methods for isolation of ribosome-loaded mRNA (24,25,33), and we analyzed polysome-associated transcripts. It is generally accepted, with few exceptions, that mRNAs associated with polysomes are actively translated (26).…”
Section: Effect Of Cr On Differential Mrna Translation In the Livermentioning
confidence: 99%
“…It is generally accepted, with few exceptions, that mRNAs associated with polysomes are actively translated (26). While some of the transcripts might escape the analysis because of some limitations of this approach, but generally changes in the transcript abundance in polysomes provide the information on the state of the cellular translatome (25). We isolated polyribosomes from livers of wild-type mice on AL and CR diets.…”
Section: Effect Of Cr On Differential Mrna Translation In the Livermentioning
confidence: 99%
See 1 more Smart Citation
“…mass cytometry | protein synthesis | tellurium M easuring spatial and temporal changes in protein synthesis is necessary to understand the function and dysfunction of multicellular organisms. Protein synthesis can be monitored using radiolabeled amino acids, functional noncognate amino acids, sequencing data from ribosome-associated mRNA, or puromycin labeling approaches (1). However, application of these methods can be complicated by the limitations of the experimental protocols.…”
mentioning
confidence: 99%